Out loud : a memoir - Morris, Mark, 1956-; Stace, Wesley (Penguin Press, 2019)
"From one of the most creative and audacious choreographers of our time, the exuberant tale of a young dancer's rise to the pinnacle of the performing arts world, and the triumphs and fiascos of creating work on his own terms--and staying true to himself. Moving to New York at nineteen, he arrived to one of the great booms of dance in America. Audiences in 1976 had the luxury of Merce Cunningham's finest experiments with time and space, of Baryshnikov's sheer artistry, of Twyla Tharp's virtuousity, and the genius of Lucinda Childs. Mark was flat broke, but found a group of likeminded artists that danced together, traveled together, slept together. No one wanted to break the spell or miss a thing: "if you missed anything, you missed everything." This collective, led by Mark's fiercely original vision, became the Mark Morris Dance Group. Out Loud is the big-hearted and outspoken story of a man as formidable on the page as he is on the boards. With unusual candor and fabulous wit, Mark's memoir captures the life of a performer who broke the mold, a maverick who found his home in the collective, liberating world of music and dance"--